Proceedings of the 2018 26th ACM Joint Meeting on European Software Engineering Conference and Symposium on the Foundations of 2018
DOI: 10.1145/3236024.3236061
|View full text |Cite
|
Sign up to set email alerts
|

Towards a theory of software development expertise

Abstract: Software development includes diverse tasks such as implementing new features, analyzing requirements, and fixing bugs. Being an expert in those tasks requires a certain set of skills, knowledge, and experience. Several studies investigated individual aspects of software development expertise, but what is missing is a comprehensive theory. We present a first conceptual theory of software development expertise that is grounded in data from a mixed-methods survey with 335 software developers and in literature on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 88 publications
2
48
0
Order By: Relevance
“…A related area of research looked into characteristics and work habits of successful developers, some of which developers might consider relevant and important to pursue as goals. Amongst other characteristics, successful developers often share similar attributes, such as striving for productivity and efficiency, being self-aware, asking for and offering help and feedback, constantly learning and self-improving, doing data-driven decisions, and setting challenging goals [1], [2], [14], [35], [49], [50]. Successful developers also manage to find a good balance between focused work and helping or mentoring others [2], [14].…”
Section: Productive Developers' Work Habitsmentioning
confidence: 99%
See 3 more Smart Citations
“…A related area of research looked into characteristics and work habits of successful developers, some of which developers might consider relevant and important to pursue as goals. Amongst other characteristics, successful developers often share similar attributes, such as striving for productivity and efficiency, being self-aware, asking for and offering help and feedback, constantly learning and self-improving, doing data-driven decisions, and setting challenging goals [1], [2], [14], [35], [49], [50]. Successful developers also manage to find a good balance between focused work and helping or mentoring others [2], [14].…”
Section: Productive Developers' Work Habitsmentioning
confidence: 99%
“…time, size, quality, schedule data), to better understand and improve their performance, quality, time estimations and skills [38]. Baltes et al recently found that many developers already selfmonitor their work, by using tools such as RescueTime [61], Codealike [71] or Wakatime [72], but only very few actively and regularly reflect on work (3 out of 204 survey participants) [14]. This is why we were interested in learning how open developers are towards actively self-reflecting on their work on a daily basis during several weeks.…”
Section: Background: Reflective Goal-settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Altogether, this triangulation with Linkedin shows that the proposed clustering-based method was able in most cases to find several GitHub developers with evidences of having experience on the studied libraries. However, before concluding, it is also important to acknowledge that expertise and experience are distinct concepts; indeed, experience is normally viewed as a necessary condition to achieve expertise [44], [45].…”
Section: Triangulation With Linkedin Profilesmentioning
confidence: 99%